Development and Characterization of a Nanocomposed Pioglitazone Hydrochloride-Loaded Niosomal Suspension for Targeted Drug Delivery - Shweta Kyadalwar; Rahul Waghmare; Kranti Satpute; Prakash Shivnechari; Shoaeb Mohammad Syed (Journal of Bio-X Research)
Background: The primary aim of this research was to address the significant challenge of low and unpredictable drug absorption following oral administration, which often occurs due to poor water solubility. Niosomes, which are lipid-based vesicles, have been explored as potential solutions to increase the solubility of water-insoluble drugs. Methods: Niosomal suspensions were prepared with the thin-film hydration method. Various concentrations of Span 20, Span 40, Tween 60, and cholesterol were used to optimize the formulation. The resulting formulations were characterized, and their properties were assessed. Results: The optimal formulation, namely, NS6, which was composed of Span 40 (200 mg) and cholesterol (40 mg), had a size of 206.1 nm and a zeta potential of −36.5 mV. Adjusting the surfactant concentration resulted in a maximum drug entrapment efficiency of 88.89%. Statistical analysis confirmed that NS6 was the optimal formulation. Conclusion: This study demonstrates that niosomal suspensions are promising drug delivery systems with potential for use in treating type 2 diabetes. Niosomes facilitate the sustained release and enhanced solubility of drugs, rendering them convenient and effective tools for enhancing drug delivery to target sites.